MANAJEMEN KEPEMIMPINAN TGH. HASANAIN JUAINI DALAM MENGEMBANGKAN PONDOK PESANTREN HARAMAIN NARMADA LOMBOK BARAT - Wildan (STIT Al-Aziziyah, 2022)
The leader in an educational institution is highly required to develop an educational institution to its intended purpose. The leader in an educational institution must be able to do his job in determining the performance of institutions, because he determines the existence and performance of an institution. TGH.Hasanain as a leader should be able to affect its members and required to respond the changes of the times. Pondok pesantren as educational institutions, on their way cannot swerve from the influence of time progress accompanied by the advancement of science and technology. Therefore, TGH.Hasanain anticipating to be able to develop pondok pesantren in to face the change of the times. The type of leadership is able to bring a very significant change for Pondok Pesantren Nurul Haramain Narmada.This research aims to uncover the type of leadership used by TGH. Hasanain Juaini in developing the institution, led by sub focus includes: (1) how leadership function of TGH. Hasanain Juaini, (2) how the efforts of TGH. Hasanain Juaini in developing educational institutions, and (3) how leadership typology of TGH. Hasanain Juaini.This research was carried out using qualitative research with case study as design of research. Data collection is done with the interview, observation, and study of the documentation. Meanwhile, the data are analyzed by interactive analysis model that are containing three steps; data reduction, data display, and conclusion. To examine the validity of the data, the researcher use triangulation of methods and triangulation of source of data.The result of this research indicates that, (1) TGH. Hasanain Juaini does the function of managerial leadership in running his leadership, namely by affecting, planning, organizing, directing, and monitoring all activities or human resources of pondok pesantren that he leads, (2) TGH.Hasanain Juaini make efforts to modernize its pondok pesantren, namely by implementing ICT as a tool of learning and teaching, and use foreign languages ( english and arabic ) as the major language of pondok Pesantren Nurul Haramain Narmada, (3) the leadership type of TGH.Hasanain Juaini is visionary leadership, it means that he has the main characteristics of visionary leadership.